The year of the flood : a novel - Atwood, Margaret, 1939- (Nan A. Talese/Doubleday, 2009)
Following a cataclysmic natural disaster, Adam One, leader of the religion known as God's Gardeners, and his followers make their way through an altered, depopulated world, while Ren, a performer trapped in a high-end sex club, and Toby, a God's Gardener barricaded inside a luxurious spa, try to decide how to proceed.